Fruit peel polyphenols demonstrate substantial anti-tumour effects in the model of breast cancer - Kubatka, Peter; Kapinová, Andrea; Kello, Martin; Kruzliak, Peter; Kajo, Karol; Výbohová, Desanka; Mahmood, Silvia; Murin, Radovan; Viera, Tischlerová; Mojžiš, Ján; Zulli, Anthony; Péč, Martin; et al. (European journal of nutrition, 2016)
PURPOSE: Fruit and vegetable intake is inversely correlated with cancer; thus, it is proposed that an extract of phytochemicals as present in whole fruits, vegetables, or grains may have anti-carcinogenic properties. Thus, the anti-tumour effects of fruit peel polyphenols (Flavin7) in the chemoprevention of N-methyl-N-nitrosourea-induced mammary carcinogenesis in female rats were evaluated. METHODS: Lyophilized substance of Flavin7 (F7) was administered at two concentrations of 0.3 and 3 % through diet. The experiment was terminated 14 weeks after carcinogen administration, and mammary tumours were removed and prepared for histopathological and immunohistochemical analysis. In addition, using an in vitro cytotoxicity assay, apoptosis and proliferation after F7 treatment in human breast adenocarcinoma (MCF-7) cells were performed. RESULTS: High-dose F7 suppressed tumour frequency by 58 % (P < 0.001), tumour incidence by 24 % (P < 0.05), and lengthened latency by 8 days (P > 0.05) in comparison with the control rats, whereas lower dose of F7 was less effective. Histopathological analysis of tumours showed significant decrease in the ratio of high-/low-grade carcinomas after high-dose F7 treatment. Immunohistochemical analysis of rat carcinoma cells in vivo found a significant increase in caspase-3 expression and significant decrease in Bcl-2, Ki67, and VEGFR-2 expression in the high-dose group. Both doses demonstrated significant positive effects on plasma lipid metabolism in rats. F7 significantly decreased survival of MCF-7 cells in vitro in MTT assay by dose- and time-dependent manner compared to control. F7 prevented cell cycle progression by significant enrichment in G1 cell populations. Incubation with F7 showed significant increase in the percentage of annexin V-/PI-positive MCF-7 cells and DNA fragmentation. CONCLUSIONS: Our results reveal a substantial tumour-suppressive effect of F7 in the breast cancer model. We propose that the effects of phytochemicals present in this fruit extract are responsible for observed potent anti-cancer activities.
Keywords: antigen Ki-67; MCF-7; modely nemocí na zvířatech; methylnitrosomočovina; bcl-2-Associated X Protein; Caspase 3; Antineoplastic Agents, Phytogenic; experimentální nádory mléčných žláz; kaspasa 3; Cell Proliferation; fragmentace DNA; receptor 2 pro vaskulární endoteliální růstový faktor; polyfenoly; Mammary Neoplasms, Experimental; vztah mezi dávkou a účinkem léčiva; MFC-7 buňky; tyrosin; protein X asociovaný s bcl-2; Cell proliferation; MCF-7 Cells; krysa rodu Rattus; stilbeny; Animals; DNA Fragmentation; ovoce; lidé; ženské pohlaví; flavonoidy; Ki-67 Antigen; Methylnitrosourea; Humans; Stilbenes; zvířata; Angiogenesis; Tyrosine; Rats; Vascular Endothelial Growth Factor Receptor-2; Disease Models, Animal; Rat; apoptóza; proliferace buněk; Mammary carcinogenesis; Flavonoids; Fruit polyphenols; Fruit; fytogenní protinádorové látky; Female; Dose-Response Relationship, Drug; Apoptosis; Polyphenols